The Appropriate Calculation Cost of Goods Manufactured as Pricing Strategy for Small Sized Enterprises (SMEs) - Adawia, Popon Rabia; Puspasari, Aprilia; Azizah, Ayu; Asep, Asep; Mustomi, Dede (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2021)
This research aims to identify all production costs incurred in production, to calculate the cost of goods manufactured correctly using the Process Costing Method and decision making for determining the selling price of shoes. The research was taken in one of small-sized enterprises shoe factory in East Karawang. The research method is descriptive comparative with a qualitative approach. The descriptive method is used to describe the production costs incurred in the production process including the raw materials costs, supporting materials costs, labor costs, and factory overhead costs. In this research, the data used are primary and secondary data. The COGM calculation results in show that there is variance calculation between company system and process costing method. It is due to calculations that companies do not identify production costs in detail, therefore the company’s COGM calculation is inaccurate. The COGM calculation appropriately can be the company’s strategy to determine the selling price. so that company profits can continue to increase.